Blockchain Enabled Voting System for Improving Election Transparency and Trust - Nasib Nasib; Fina Nailatul Izzah; Aldila Dinanti; Az Zahrawani Ramadhan; Ikyboy Van Versie (Blockchain Frontier Technology, 2026)
Elections are a fundamental component of democratic systems, yet conventional paper based and centralized electronic voting mechanisms continue to face persistent challenges related to transparency, security, auditability, and declining public trust. To address these issues, this study aims to design and evaluate a blockchain enabled voting system that can improve election transparency and strengthen voter trust by leveraging decentralization, immutability, and crypto- graphic security. The research adopts a system design and evaluation methodology that integrates an in depth literature review, blockchain architecture modeling, smart contract development, and experimental evaluation focusing on security, transparency, and performance under simulated election conditions. The results show that the proposed system successfully ensures immutable vote recording, prevents double voting through automated smart contract enforcement, enhances end to end auditability via a transparent distributed ledger, and significantly improves resistance to vote manipulation and unauthorized access when compared to conventional and centralized electronic voting systems. Performance analysis indicates that while transaction latency increases with higher voting loads due to consensus mechanisms, the system remains stable, reliable, and operational, demonstrating feasibility for small to medium scale elections. Furthermore, the decentralized architecture reduces single points of failure and minimizes reliance on trusted third parties. Overall, this study concludes that blockchain technology provides a robust and trustworthy foundation for modern digital voting systems, while also highlighting scalability, computational overhead, and real world implementation challenges that should be addressed through optimization techniques and pilot deployments in future research.